Proposal of Three-Phase High Frequency Transformer Isolation UPS Topologies - Branco, Carlos G. C.; Torrico-Bascopé, René P.; Cruz, Cicero M. T.; Lima, Francisco K. A. (Eletrônica de Potência, 2011)
A family of double conversion three-phase uninterruptible power system with power factor correction and high-frequency transformer (HFT) isolation topologies is presented in this work. This might be an alternative compared to large conventional UPS systems that are based in bulky transformers that operates in the grid frequency. These systems are suitable for operation with line-to-line input voltages equal to 220-V or 380-V. For both input voltages, the proposed converter has almost the same efficiency processing the same output power. The three-phase HFT UPS used for further analysis is composed by single-phase chopper modules, one three-phase boost module, and one three-phase inverter. The relevant features are soft commutation of the controlled switches in the chopper stage, simple control strategy that can be implemented with well-known integrated circuits (IC), and the use of few batteries in series due to the same reference of the step-up stages. Principle of operation of the chosen system for experimental validation, implemented control strategy and experimental results obtained for a 15kVA prototype are presented.